Real-time processing of passives versus actives: different patterns during form retrieval and meaning construction. - Hwang, Haerim; Han, Ganling (Language, Cognition & Neuroscience, 2026)
Despite the impression that we use a uniform approach to understanding sentences, humans' processing strategies adjust based on the specific tasks. This study employs two task types that have been rarely used in previous research on passives, which are non-canonical compared to actives and are arguably prone to misinterpretations. A fill-in-the-blank task, where heuristic, surface-level parsing strategies may be adequate for form retrieval, shows no differences in English speakers' accuracy or response times for passives versus actives. However, the participants responded more accurately and faster to passives with the additional cue of an agent than they did to agentless passives. In a visual-world eye-tracking task, which may involve algorithmic parsing strategies for meaning construction, the same participants showed slower processing of passives compared to actives. These findings indicate that the processing routines engaged during different task types influence the way sentences are processed.